2020
DOI: 10.15243/jdmlm.2020.072.2095
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship of land carrying capacity and building area towards the development of Kualanamu International Airport in 2010 and 2017

Abstract: Land resources availability has been declining due to the rapid development of the industrial, residential, and even tourism sectors in all regions, including Batang Kuis Subdistrict, Deli Serdang Regency of North Sumatra Province. The declining of land resources in Batang Kuis Subdistrict has a strong relationship with the factors causing rapid and dynamic development of Kualanamu Airport located at the east side of the sub-district. Regional development causes land conversion and urban development that impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…According to the key informants, the main factors that determined the degradation of mining land in the study area were: lack of local community involvement in land management practices, lack of environmental rules and regulations, difficulties in recording small and large scale mining activity, lack of environmental education, etc. This finding is confirmed by Christianawati et al. (2020) whose study revealed that there were no nationally recognized standards for institutions for mining regulatory frameworks.…”
Section: Resultsmentioning
confidence: 77%
“…According to the key informants, the main factors that determined the degradation of mining land in the study area were: lack of local community involvement in land management practices, lack of environmental rules and regulations, difficulties in recording small and large scale mining activity, lack of environmental education, etc. This finding is confirmed by Christianawati et al. (2020) whose study revealed that there were no nationally recognized standards for institutions for mining regulatory frameworks.…”
Section: Resultsmentioning
confidence: 77%
“…The carrying capacity is the capability of agricultural land to be able to support the food needs of the population of a region. Carrying capacity is also a description of the conditions between population, area of agricultural land and the surrounding environment and can estimate the need for agricultural land that is able to provide sufficient food for each resident in a certain period [5]. The fulfillment of sufficient food for each individual is also known as food security.…”
Section: Introductionmentioning
confidence: 99%